Structural integration as a method holistic impact on the myofascial system - Natański, Dawid; Ożóg, Piotr; Zukow, Walery; Goch, Aleksander (Journal of Education, Health and Sport, 2018)
Myofascial tissue in recent years has aroused great interest. Evidenced by the increase in the amount of research on it. Modern studies provide a large amount of information on this tissue. Initially underestimated and imported exclusively to muscle tissue sheaths, modern science reveals a completely new face. Recent studies show that it is involved in the creation of various structures such as the even: straps, ligaments and joint capsules. These results shed a completely new light on the impact of the fascial tissue for organ motion.For a full understanding of continuity, complexity and the role of fascial tissue for the locomotor system should take into account the distribution of such tissue in relation to the various "layers", in which it occurs. The overall breakdown is as follows: superficial fascial tissue - reticular, deep fascia, epimysium, perimysium and endomysium.The concept tensegration, which is derived from a combination of English words and tension- tension integity - integrity, first described by Richard Buckminster Fuller and Snelson Kenteha. Its essence in the simplest way to introduce referring to the building, which consists of rigid elements and flexible joints. Actuation force on any element of the system tensegrational degrades the forces applied to more structure elements. Buildings based on this principle derive a significant resistance to external forces. An example might be the Golden Gate Bridge in San Francisco, thanks to its structure based on the principle can withstand strong earthquakes.The main objective of the therapist to strike a balance of structural and appropriate arrangement of the various parts of the body in the gravitational field. Therapy myofascial tissues are very interesting form of therapy. Following through its holistic impact distinguishes it from the classical approach of manual therapy, which focuses mostly on local disturbances. Through the use of this form of therapy it is possible to obtain stable therapeutic effects. Reduction in local or global disturbance of soft tissue tension. Therapy improves posture and pattern of global traffic patterns economy translating into traffic. So that the structural integration is a therapy that is dedicated not only to people suffering from pain. Following through its holistic impact of the success it can be used in people who want to influence the attitude correction. An interesting direction seems to be the use of musculo-fascial therapy in athletes.